2021
DOI: 10.1111/1750-3841.15845
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different alcohol and ultrasonic treatments on thermal and structural properties of zein‐starch sodium octenyl succinate composite nanoparticles

Abstract: The objective of this study is to prepare zein/starch sodium octenyl succinate composite nanoparticles (ZSPs) via anti-solvent precipitation technology and characterize their colloidal properties. The effects of polar solvents, ultrasonic treatment time, and concentrations of starch sodium octenyl succinate were investigated. We measured the particle size distribution, hydrophobicity, and apparent structures of the composite nanoparticles. Ultrasonic treatment time (0-25 min) was found to play an important rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 56 publications
(75 reference statements)
1
0
0
Order By: Relevance
“…The maximum thermal degradation temperature of the composite nanoparticles was lower than that of zein and HP-β-CD nanoparticles, indicating that complexation improved the thermal stability of the system 30 . The maximum thermal degradation temperature of QCZH was close to that of zein-HP-β-CD, but when the temperature was increased to 250 °C, the mass loss of QCZH was significantly lower than that of zein-HP-β-CD, mainly because the core-shell nanostructure containing nutrient molecules had a tighter binding effect, which was consistent with the results reported in the study of Lai et al 32 .
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…The maximum thermal degradation temperature of the composite nanoparticles was lower than that of zein and HP-β-CD nanoparticles, indicating that complexation improved the thermal stability of the system 30 . The maximum thermal degradation temperature of QCZH was close to that of zein-HP-β-CD, but when the temperature was increased to 250 °C, the mass loss of QCZH was significantly lower than that of zein-HP-β-CD, mainly because the core-shell nanostructure containing nutrient molecules had a tighter binding effect, which was consistent with the results reported in the study of Lai et al 32 .
Fig.
…”
Section: Resultssupporting
confidence: 90%
“…In addition to the commonly used aqueous ethanol solution, aqueous isopropanol solution, aqueous acetone solution, lactic acid, and glacial acetic acid all can be used as solvents for prolamin film-forming solutions [39]. Different organic solvents have different polarities, and their main functional groups are hydroxyl, carboxyl, and carbonyl groups, respectively, which carry different electronegativities, thus affecting the folding and unfolding of hydrophobic long chains of prolamins as well as their state of dissolution and dispersion in solution [41]. Nathania et al [42] investigated the effect of solvent polarity on the film properties of kafirin and showed that with reduced solvent polarity, the α-helical of kafirin in the solvent tends to increase but the water contact angle increases.…”
Section: Preparation Of Coating Solutionsmentioning
confidence: 99%
“…However, the zein/OSA-modified starch complex nanoparticles aggregated as the NaCl concentration increased, even though the addition of OSA-modified starch improved the stability of zein. Another piece of research has focused on the effects of preparation conditions (polar solvents, ultrasonic, and concentrations of OSA-modified starch) on the solubility and thermal stability of zein/OSA-modified starch complex nanoparticles [16]. However, no publications on zein/OSA-modified starch complex nanoparticles focus on their stability against pH variations, even though the instability of zein at the pI has been emphasized.…”
Section: Introductionmentioning
confidence: 99%